Influence of State of Alarm Caused by COVID-19 on Noise in the City Centre of Huelva (Spain) - FORTES, Juan Carlos; SÁNCHEZ-SÁNCHEZ, Rafael; BOLÍVAR, Juan Pedro (Archives of Acoustics, 2022)
At the beginning of the COVID-19 pandemic the government of Spain decreed the State of Alarm to confine the entire population at their homes, except for essential services. Therefore, the central objective of this study is to evaluate the implication of this situation for the environmental noise existing in the city of Huelva (Spain). This study demonstrates that during the state of alarm an average daily reduction of 3.4 dBA was noted, and in the central moments of the day these reductions reached up to 4.4 dBA, while from 10:00 to 12:00 pm the reduction was around 6.5 dBA. Nevertheless, there were two moments of day: 3:00 am (garbage collection, street cleaning and container disinfection), and 8:00 pm (daily applause for health professionals), when the noise during the pandemic was higher than before it. It is further shown that globally, the loudest events only decreased by about 3 dBA, while the global background noise decreased by 10 dBA during the alarm state. Regarding road traffic noise, it is verified that in addition to being reduced by about 4 dBA, traffic represents 6.7% of noisy events during the alarm state, while before it represented 13%.